Genetic structure and relationships among Melissa officinalis accessions using AFLP markers. (November 2019) - Danaeipour, Zahra; Fotokian, Mohammad Hossein; Talei, Daryush; Mohammad naji, Amir
Abstract: Melissa officinalis, a member of the Lamiaceae family, is one of the most important medicinal herbs that are applied in different fields of industry worldwide. Genetic diversity and structure of 21 M. officinalis accessions were examined using amplified fragment length polymorphism (AFLP) markers. For this purpose, 15 primer combinations generated a total of 1592 scorable bands, of which 1402 bands were polymorphic. The primer combination P66 /M48 showed the highest markers polymorphism values (PIC = 0.28, DI = 0.34, and I = 0.51), while the lowest values (PIC = 0.17, DI = 0.20, and I = 0.32) is obtained from the P14 /M49 combination. The marker index (MI) values with an average of 18.46 showed high values for both primer combinations E/M and P/M. All of the accessions, based on Neighbor-Net clustering method and structure analysis, are assigned to five clusters; with the maximum genetic dissimilarity of 0.51 belonging to accessions from Gilan (Roodbar and Damash). In addition, the principal coordinate analysis (PCoA) data confirmed the results of the clustering. In this study, the genetic distance was not often related to geographical distance. More likely the relationship among them is due to seed dispersal through human interactions. Our findings indicate that high genetic diversity of M. officinalis accessions provides important baseline data and a better understanding of conservation, management, and collection strategies for germplasm of this species. Highlights: AFLP showed high genetic diversity among M. officinalis accessions. AFLP markers can be effectively used for investigation the genetic relationships in M. officinalis. Damash and Roodbar accessions with the highest genetic diversity had completely different background. Fourteen accessions were the genetic background of Hungary accession showing genetic combinations of them. High diversity provides important baseline data for the germplasm management of this species.